Etiquette and vitriol the Food chain and other plays - Silver, Nicky 1960- (Theatre Communications Group, 1996)
The first collection by a master of razor-sharp wit and black humor, Etiquette and Vitriol brings together two of Silver's highly acclaimed and successful works - the long-running Off-Broadway hit The Food Chain and the award-winning Pterodactyls - with two earlier works - Fat Men in Skirts and Free Will & Wanton Lust - which helped establish Silver as one of the leading comic voices of his generation.
Enth. u.a.: The food chain. Pterodactyls
Keywords: Geschichte 1900-2000; American drama -- 20th century